TV 3.0: Integração e Controle de Renderizadores de Efeitos Sensoriais - Ivanov, Marina; Vieira, Rômulo; Santos, Joel A. F. dos; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Advancements in the Brazilian television sector have been consistently intertwined with the technological innovations of each era. From its inception, supporting only live broadcasts, through the integration of recorded content on magnetic tapes, to the adoption of a color standard, television broadcasts have always been driven by the pursuit of higher quality. Currently, the Brazilian Digital Terrestrial Television System Forum (SBTVD) is working on a new national standard, referred to as TV 3.0, which, among various guidelines, aims to incorporate multiple secondary devices, such as sensory effect actuators, to enhance immersion and provide viewers with a richer content experience. In this context, the present paper proposes architectural changes to the TV receiver, a communication protocol, and an Application Programming Interface (API) to control various functions in sensory effect display devices, such as activation, deactivation, and adjustments in renderings. Additionally, a use case is presented to validate these concepts and demonstrate how they may find full applicability in the next generation of digital terrestrial television in Brazil.